Clays and Clay Minerals, Vol. 60, No. 2, 186–199, 2012. - Marston, Thomas M.; Parry, W. T.; Bowman, John R.; Solomon, D. Kip (The Clay Minerals Society, 2012)
The presence, percentage, origins, and rate of formation of clay minerals have been important components in studies involving the geochemical and structural composition of waste-rock piles. The objective of the present study was to investigate the use of tritium as an indicator of the origin of clay minerals within such piles. Tritium values in pore water, interlayer water, and structural hydroxyl sites of clay minerals were examined to evaluate the origins of clay minerals within waste-rock piles located near Questa, New Mexico. Five clay minerals were identified: kaolinite, chlorite, illite, smectite, and mixedlayer illite-smectite, along with the hydrous sulfate minerals gypsum and jarosite. Analysis of waters derived from clay minerals was achieved by thermal reaction of dry-sieved bulk material obtained from the Questa site. In all Questa samples, the low-temperature water derived from pore-water and interlayer sites, as well as the intermediate-temperature water derived from interlayer cation sites occupied by hydronium and structural hydroxyl ions, show tritium values at or near modern levels for precipitation. Pore water and interlayer water ranged from 5.31 to 12.19 tritium units (TU) and interlayer hydronium and structurally derived water ranged from 3.92 to 7.93 TU. Tritium levels for local precipitation ranged from ~4 to 8 TU. One tritium unit (TU) represents one molecule of 3H1HO in 1018 molecules of 1H1HO. The elevated levels of tritium in structural sites can be accounted for by thermal incorporation of significant amounts of hydronium ions in interlayer cation sites for illite and mixed-layer clays, both common at the Questa site. In low-pH environments, such as those found within Questa waste-rock piles (typically pH ~3), the hydronium ion is an abundant species in the rock-pile pore-water system.
Tritium Content Of Clay Minerals
gsccm60208-mar.pdf -- 1,992KB
Keywords: Periodicals; Geology; Formation Age; Hydronium; Interlayer Water; Isotopic; Tritium; Slope Stability; Structural Hydroxyl